Synovial sarcoma relapses in children and adolescents: Prognostic factors, treatment, and outcome. Issue 8 (24th March 2014) - Soole, Frederick; Maupain, Carole; Defachelles, Anne‐Sophie; Taque, Sophie; Minard‐Colin, Veronique; Bergeron, Christophe; De Rycke, Yann; Orbach, Daniel
<x xml:space="preserve">Abstract</x> Introduction Twenty‐five to 32% of patients with synovial sarcoma (SS) relapse after appropriate treatment, and experience a poor outcome. Patients who can be salvaged by second‐line therapy need to be more clearly identified. Patients and Methods Data of patients treated in SFCE (Société Française des Cancers de l'Enfant) centers with an initial diagnosis of localized SS before the age of 18 years and treated from 1/1988 to 12/2008, and who experienced at least one relapse, were retrieved. After descriptive analysis, statistical analysis was performed to determine prognostic factors. Results Thirty‐seven patients were identified. First relapse occurred after a median interval of 24 months and was localized in 73.0% of cases and metastatic in 24.3% of cases. Treatment of relapse consisted of new surgery in 75.7% of cases, second‐line chemotherapy in 73.0% of cases and radiotherapy in 48.6% of cases. Response rate to ifosfamide‐based regimens was 36.4%. Overall, 70.3% patients achieved a second complete remission. Median 5‐year‐event‐free survival was 32.8% and 5‐year overall survival was 42.1%. Factors significantly correlated with better survival were primary tumor involving the limbs, age less than 12 years at diagnosis, absence of chemotherapy or radiotherapy as initial treatment and local relapse. Conclusion Despite its poor overall outcome, relapse of synovial sarcoma sometimes remains curable. Aggressive surgery, when possible, in combination with chemotherapy and radiotherapy is the recommended treatment. Ifosfamide‐based regimens may remain effective in patients with relapsed SS. However, alternative therapies should be proposed in patients with poor prognostic factors. Pediatr Blood Cancer 2014; 61:1387–1393. © 2014 Wiley Periodicals, Inc.